Random Choice from Likelihood: The Case of Chuj (Mayan). (29th October 2021) - Alonso-Ovalle, Luis; Royer, Justin
Abstract: Research on modality has recently broadened beyond the verbal domain, unearthing questions about the cross-categorial nature of modality ( Arregui et al. 2017 ), for instance: To what extent do DP and VP modals mirror each other? Chuj, an understudied Mayan language, provides an ideal vantage point to answer this question with respect to random choice modality. Random choice indefinites convey, roughly, that an agent made an indiscriminate choice. In Chuj, random choice indefinite DPs involve a morpheme ( komon ) that can also appear as a verbal modifier (Royer & Alonso-Ovalle 2019 ), inviting a comparison between categories. We argue that both in DPs and VPs, komon conveys information about the likelihood of the event described, but that the modal component of komon is nevertheless tied to its syntactic position. VP- komon conveys that the most expected worlds where the described event happens are no more expected than the most expected worlds where it does not. DP- komon conveys a similar modal component, but hardwires a comparison between the likelihood of the event described, which involves an individual in the extension of the NP, and that of alternative events determined by considering alternative individuals in the extension of that NP. The characterization of the modal component of komon contributes to the characterization of random choice modality and brings into question whether this type of modality should be taken to be a unified category, since none of the previous proposals on the nature of random choice modality tie it to the expression of likelihood.